Analisis Perbandingan Detektor Geiger Muller dan Scintillation dalam Aplikasi Klinik dan Proteksi Radiasi di Rumah Sakit - Aisya Villea Rania Az Zahra; Dzakya Ilmi; Erlinda Ratnasari Putri (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2026)
The use of ionizing radiation in medical procedures requires accurate and reliable monitoring to ensure the safety of healthcare workers and patients. Radiation detectors such as Geiger–Müller (GM) and scintillation detectors are widely utilized in hospitals, yet they differ significantly in their working principles, sensitivity, and suitability for clinical and protection purposes. This study aims to compare the performance of GM and scintillation detectors through a literature review approach. Articles were collected from Google Scholar using keywords related to GM detectors, scintillation detectors, clinical applications, and radiation protection. Selected studies were examined based on operational mechanisms, sensitivity, dose-rate range, energy discrimination capability, and practical use in hospital settings. The analysis shows that GM detectors operate through gas ionization and produce pulses of uniform amplitude, enabling only the counting of radiation events without providing energy information. These characteristics make GM detectors more appropriate for environmental surveillance, background monitoring, and high-dose alert systems due to their wide measurement range and stable response. In contrast, scintillation detectors such as NaI(Tl) generate light output proportional to the absorbed energy, allowing spectral analysis, radionuclide identification, and more accurate dose assessment. Their high sensitivity and superior energy resolution make them more suitable for clinical tasks, including gamma spectroscopy, nuclear medicine imaging, radiotherapy dose verification, and beam quality assessment. Overall, GM detectors are advantageous for routine radiation protection monitoring, while scintillation detectors are preferred for clinical applications requiring precise measurement and energy characterization.